The evolution of personalized stroke thrombectomy - Mensah, Emmanuel O.; Fong, Yew-Weng; Muram, Sandeep; Ogilvy, Christopher S.; Taussky, Philipp (Frontiers in Surgery, 2025)
Stroke is a leading cause of disability and death worldwide, with acute ischemic stroke accounting for most cases. Mechanical thrombectomy is a widely accepted treatment modality in appropriately selected patients, demonstrating improved functional outcomes through safe and effective recanalization. However, traditional trials have focused on a narrow subset of patients, limiting its applicability to diverse populations who would otherwise benefit from thrombectomy. Advances in neurovascular imaging, device innovation, and procedural techniques are driving a paradigm shift toward personalized stroke thrombectomy. This review explores personalization strategies across various domains, including lesion-specific considerations such as medium vessel occlusions (MeVOs), basilar artery occlusions (BAOs), and tandem lesions, as well as patient-specific factors like infarct size, low NIHSS scores, advanced age, and unique biomarkers. Additionally, we discuss procedural innovations, such as tailored device use and alternative access strategies to address anatomical and clinical complexities. While substantial progress has been made, challenges remain in refining patient selection criteria, mitigating procedural risks, and ensuring equitable access to thrombectomy. Future directions include taking full advantage of advanced imaging modalities, incorporating biomarkers for personalized care, and optimizing thrombectomy devices to support the use of thrombectomy in underrepresented populations. Precision thrombectomy has the potential to be adapted to a broader spectrum of patients, improving outcomes and ultimately reducing the global burden of stroke.